Business strategy, strategic role of accountant, strategic management accounting and their links to firm performance: an exploratory study of manufacturing companies in Malaysia / Tan Ah Lay and Ruzita Jusoh - Tan, Ah Lay; Jusoh, Ruzita (Accounting Research Institute (ARI), 2012)
Despite that there is no agreed theoretical framework for strategic management accounting (SMA), the academics generally agree that SMA is external long-term focused, assists managers in the strategic decision-making process. This exploratory study investigates the mediating effect of SMA on the relationship between Porter's (1980) competitive strategy and firm performance. The contingency model incorporates the two dimensions of SMA, i.e. the usage of SMA techniques and the changing role of accountants in the strategic decision-making process. The results of partial least squares appear to support SMA usage mediates partially the relationship between product differentiation strategy and firm performance. There is also a positive relationship between business strategy and strategic role of accountant. However, it is unable to find support on the positive association between strategic role of accountant and firm performance.